Mechanism Action of Platelets and Crucial Blood Coagulation Pathways in Hemostasis - Mercy Halleluyah Periayah; Ahmad Sukari Halim; Arman Zaharil Mat Saad (International Journal of Hematology-Oncology and Stem Cell Research, 2017)
Blood is considered to be precious because it is the basic necessity for health; our body needs a steady provision of oxygen, supplied via blood, to reach billions of tissues and cells. Hematopoiesis is the process that generates blood cells of all lineages. However, platelets are the smallest blood component formed in the bone marrow and play a fundamental role in thrombosis and hemostasis. Platelets contribute their hemostatic capacity via adhesion, activation and aggregation, which are triggered upon tissue injury, and these actions stimulate the coagulation factors and other mediators to achieve hemostasis. In addition, these coordinated series of events are the vital biological processes for wound healing phases. The aim of this review is to summarize and highlight the important pathways involved in achieving hemostasis that are ruled by platelets. In addition, this review also describes the mechanism action of platelets, including adhesion, activation, aggregation, and coagulation, as well as the factors that contribute to hemostasis and wound healing.